Evaluasi dan Optamasi Electrical Submersible Pump pada Sumur PR-07 LapangaN AB - Asbahul Badya; Fatma; Adelia Rohani (Kodepena (Komunitas Dosen Penulis dan Peneliti Indonesia), 2026)
ESP as an artificial lift system plays an important role in optimizing oil production; therefore, an evaluation and optimization were conducted on Well PR-07, AB Field to assess pump performance and determine the optimum production rate. The analysis was carried out using the Vogel method on the Inflow Performance Relationship (IPR) curve, resulting in a maximum production rate (Qmax) of 2,441.79 BFPD and an optimum production rate (Qo) of 1,953.43 BFPD. Current well conditions show a water cut of 82%, resulting in an oil flow rate of only about 202 BOPD. The pump applied is 134-400 CENTURION FLEX 17-5SXD with 52 stages, which is still suitable in terms of capacity. However, the high water content is the main limiting factor for oil production, so optimization efforts are focused on determining the optimum flow rate, controlling water cut, and monitoring ESP performance to maintain operational reliability and improve production efficiency.